Robust diversity-combining receivers for wireless systems over fading channels - Heng, Lester Soon Chye (Nanyang Technological University, 2024)
The wireless communication systems working in real-world scenarios must deal with many challenges like multipath propagation and fading channel. This report discusses the modulation performance in both Rayleigh and Rician fading channels considered in combination with Additive White Gaussian Noise (AWGN). The Rayleigh fading channel, which has no LOS component, is very different from Rician fading, where signals having LOS coexist with multipath-faded signals. Mathematical derivations combined with simulations illuminate Rayleigh and Rician fading probability density functions, thus exposing their uniqueness. Different modulation schemes, such as Binary Phase Shift Keying (BPSK) and Quadrature Amplitude Modulation (QAM), are investigated in such scenarios to illustrate the bit error rate dependency on the channel characteristics. The simulated outcomes, with increased K-factors for the Rician fading that shows stronger LOS components, have better BER performance. Moreover, the effectiveness of combining techniques including Maximum Ratio Combining (MRC), Equal Gain Combining (EGC), and Selection Combining (SC) in tackling fading problems is also assessed. MRC and EGC reveal enhancement in BER performance at higher K-factors, while SC is tech lags, hence selecting the right diversity combining technique based on channel conditions and modulation schemes is essential. More studies are recommended to identify the most important parameters impacting modulation capabilities in fading channels and then developing robust communication systems withstand adverse channel conditions.